The cytokine and chemokine expression profile of nucleus pulposus cells: implications for degeneration and regeneration of the intervertebral disc - Phillips, Kate L E (BioMed Central, 2013)
INTRODUCTION: The aims of these studies were to identify the cytokine and chemokine expression profile of nucleus pulposus (NP) cells and to determine the relationships between NP cell cytokine and chemokine production and the characteristic tissue changes seen during intervertebral disc (IVD) degeneration. METHODS: Real-time q-PCR cDNA Low Density Array (LDA) was used to investigate the expression of 91 cytokine and chemokine associated genes in NP cells from degenerate human IVDs. Further real-time q-PCR was used to investigate 30 selected cytokine and chemokine associated genes in NP cells from non-degenerate and degenerate IVDs and those from IVDs with immune cell infiltrates (‘infiltrated’). Immunohistochemistry (IHC) was performed for four selected cytokines and chemokines to confirm and localize protein expression in human NP tissue samples. RESULTS: LDA identified the expression of numerous cytokine and chemokine associated genes including 15 novel cytokines and chemokines. Further q-PCR gene expression studies identified differential expression patterns in NP cells derived from non-degenerate, degenerate and infiltrated IVDs. IHC confirmed NP cells as a source of IL-16, CCL2, CCL7 and CXCL8 and that protein expression of CCL2, CCL7 and CXCL8 increases concordant with histological degenerative tissue changes. CONCLUSIONS: Our data indicates that NP cells are a source of cytokines and chemokines within the IVD and that these expression patterns are altered in IVD pathology. These findings may be important for the correct assessment of the ‘degenerate niche’ prior to autologous or allogeneic cell transplantation for biological therapy of the degenerate IVD.